PEMAHAMAN MASYARAKAT TERHADAP PORNOAKSI ( KASUS PERTUNJUKAN MUSIK ORGEN TUNGGAL) DI DESA KOTO SIPOPAK,KECAMATAN TANJUNG BARU KABUPATEN TANAH DATAR - Satria Dodi; Siti Sofro Siddiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The study was motivated by a single orginal show.The phenomenon occurred in the Village Koto Sipopak, Tanjung Baru District, Tanah Datar Regency. The purpose of this study is to determine the understanding of the community against porn action performances orgen tunggal music, Knowing the Impact caused by Orgen Tunggal music performance. This research uses descriptive qualitative method. the sample in this research using proposif sampling method. The result of this research is the perception of society to single organs which is considered as a form of deviation from social norm, culture, even religion. On the other hand it becomes part of society, whose presence is needed both for the visitors. Nor the owner and artist elekton who expect to get additional tips from the audience other than that he got from the job given the owner of elekton. The impact of the presence of organ tunggal music varies between them. There is a shift in values and norms prevailing in the local area. May impair the moral formation of children because single orgen music performances are held in open areas without any restrictions. Lost laziness to the audience after watching a single orgen music performance because the show held until morning, The emergence of a sense of parental concern to his sonKeywords: Public Understanding, action porn,village Koto Sipopak